Add value to your training skills in food processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Training in Food Processing: Successful Approaches. CTA-Intermediate Technology Publications co-publication. 1998. 135 pp. ISBN 1-85339-425-4 CTA number 900, 20 credit points